Satisfação dos idosos em tratamento de câncer acerca dos cuidados de enfermagem na hospitalização - ALENCAR, Larissa Cristina Rodrigues (2019)
Patient satisfaction can be understood as the comparison of their expectations with perceptions about meeting the actual service. To know the impact of the disease and the treatment on the life of these elderly people is essential for the planning of actions that aim at the adequate attendance of their needs. The objective of this study is to evaluate the satisfaction of the elderly with cancer about the nursing care during the hospitalization. A descriptive, cross-sectional study with a quantitative approach was carried out. The sample consisted of 365 elderly men and women, diagnosed with cancer and hospitalized at a High Complexity in Oncology Center in. Two instruments were used to collect data, one being the socioeconomic, demographic and clinical questionnaire and the other the Patient Satisfaction Instrument. The collected data was organized in spreadsheets of the program Microsoft Office Excel® 2013 for Windows 2010 already with automatic conversion of scores. Data Analysis and Statistical Software (STATA®) version 14.0 was used for descriptive and inferential analysis. Regarding the results obtained, the prevalence of males, aged 60-69 years, brown, retired, from other municipalities of the state, incomplete elementary school, married / stable union, income between 1 and 2 minimum wages, prevalence of prostate and skin cancer, surgical treatment, ex-smokers and alcoholics. They presented a good index of satisfaction (3.56), with emphasis in the technical-professional domain. There was an association between the variables gender, color, origin, income, history of cancer in the family, smoking and alcohol consumption with nursing care. It is important to note the importance of the nurse to know the satisfaction of elderly patients in cancer treatment, since their care, besides being humanized, should be focused on their particularities, as well as the factors that influence their level of satisfaction, in order to establish a bond of trust with those who take care of and consequently favor a positive evaluation of the care that this elderly person receives.